Effect of Time of Harvest and Seed Size on Seed Quality of Soybean - Harnowo, Didik (2004)
Soybean is one of the most important legume crop in Indonesia. It is widely cultivated in several agro-ecosystems to meet the local needs. The availability of high quality seeds is essential for increased productivity but is often neglected. Farmers use seeds from the previous planting irrespective of season, harvest time and bulk seeds of varying size together. This study was undertaken in three step wise experiments in order to study the effect of the current practices on seed quality, namely (1) to understand the effect of production environment (wet and dry seasons) and time of harvest on seed quality, (2) to study the effect of seed size within cultivar on seed quality, and (3) to determine the agronomic performance of seed lots within cultivar differing in seed size. Seed quality was assessed using the value of its potential longevity (Ki, in probit scale), the intercept of the transformed seed survival curve into probit scale. Production environment affected seed quality, whereby seeds produced in wet season had lower quality than those in dry season, as indicated by lower seed potential iv longevity (Ki). The response of six soybean cultivars to production environment on seed size and crop duration was similar. Physiological maturity or mass maturity occurred at around developmental stage R6 + 15 days while maximum seed quality occurred five days later. Since farmers generally harvest soybean at around developmental stage R6 + 15 days, delaying harvest until some time after mass maturity will ensure better seed quality. Seed quality as indicated by Ki value positively correlated with oligosaccharides, especially raffinose but negatively correlated with monosaccharides as noted between seasons, among cultivars and harvest times. On the other hand, the relative amount of pectin methyl esterase (PME) negatively correlated with seed potential longevity. This suggests that oligosaccharides and PME play a role in determining quality of seed. Small sized seeds within cultivar comprised 13.8 – 16.5% of total seed produced and they exhibited lower quality than large seeds. This is largely attributed to late pollination and thus resulting in shorter grain filling period. Large and medium sized seeds within a cultivar did not differ much in quality but large seeded cultivars had much lower Ki value, indicating poorer storability. If such seeds are to be stored, more attention in relation to storage condition should be given as compared to small seeded cultivars. Differences in seed quality as shown by the Ki value correlated positively with oligosaccharides and negatively with pectin methyl esterase (PME). Interestingly, when the data of soluble sugars and PME from the first and the second experiments were pooled, and a simple linear model relating seed potential longevity with soluble sugars and PME was constructed, the content of raffinose in seeds had strong contribution to seed potential v longevity, whereas PME had smaller contribution. These two biochemical substances could explain 75% of the variation in seed potential longevity. Thus, the changes in both the content of raffinose and the relative amount of PME in seed may partly explain the changes in seed potential longevity due to the difference in production environment, time of harvest, and seed size. Cultivars responded differently in its agronomic performance when planted under optimal condition. Plants from large sized seeds had better growth parameters as compared to those from small sized seeds. Therefore, bulking should not be practiced, rather the 15% of small sized seeds should be removed from the seed lot. Since soybean cultivation is a big industry in Indonesia, the establishment of a seed program should be initiated. Based on the results of the present study, this thesis provides a strong basic knowledge to help in establishment of a seed production plan, namely (1) seed production should be carried out in dry condition (dry season) i.e. during early dry season (EDS) or late dry season (LDS), (2) harvesting seeds should be done when the quality is at its maximal i.e. about five days after physiological maturity, (3) post harvest seed handling should be carried out properly especially for large seeded cultivars due to their faster deterioration rate and (4) grading should be done to exclude around 15% of small sized seeds. The above mentioned factors will ensure more uniform seed lot in terms of seed size, quality and stand establishment